Conductive Self-Assembled Monolayers of Paramagnetic CoIICo4III and Co4IICo2III Coordination Clusters on Gold Surfaces - Schmitz, Sebastian; Qiu, Xinkai; Glöß, Maria; van Leusen, Jan; Izarova, Natalya V.; Nadeem, Muhammad Arif; Griebel, Jan; Chiechi, Ryan C.; Kögerler, Paul; Monakhov, Kirill Yu. (Frontiers in Chemistry, 2019)
Two polynuclear cobalt(II,III) complexes, [Co5(N3)4(N-n-bda)4(bza·SMe)2] (1) and [Co6(N3)4(N-n-bda)2(bza·SMe)5(MeOH)4]Cl (2), where Hbza∙SMe = 4-(methylthio)benzoic acid and N-n-H2bda = N-n-butyldiethanolamine, were synthesized and fully characterized by various techniques. Compound 1 exhibits an unusual, approx. C2-symmetric CoIICoIII4 core of two isosceles Co3 triangles with perpendicularly oriented planes, sharing a central, high-spin CoII ion residing in a distorted tetrahedral coordination environment. This central CoII ion is connected to four outer, octahedrally coordinated low-spin CoIII ions via oxo bridges. Compound 2 comprises a semi-circular CoII4CoIII2 motif of four non-interacting high-spin CoII and two low-spin CoIII centers in octahedral coordination environments. Self-assembled monolayers (SAMs) of 1 and 2 were physisorbed on template-stripped gold surfaces contacted by an eutectic gallium-indium (EGaIn) tip. The acquired current density–voltage (I–V) data revealed that the cobalt-based SAMs are more electrically robust than those of the previously reported dinuclear CuIILnIII complexes with Ln = Gd, Tb, Dy or Y (Schmitz et al., 2018). In addition, between 170 and 220 °C the neutral, mixed-valence compound 1 undergoes a redox modification, yielding a Co5-based coordination cluster (1-A) with five non-interacting, high-spin octahedral CoII centers as indicated by SQUID magnetometry analysis in combination with X-ray photoelectron spectroscopy and infrared spectroscopy. Solvothermal treatment of 1 results in a high-nuclearity coordination cluster, [Co10(N3)2(N-n-bda)6(bza·SMe)6] (3), containing ten virtually non-interacting high-spin CoII centers.